Who Drives Rural Spatial Commodification? A Case Study of a Village in the Mountainous Region of Southwest China - Huicong Liu; Guoqing Shi; Weidong Xiao (Land, 2025)
Against the historical background of the rural revitalization strategy and coordinated regional development, rural characteristic industries constitute the fundamental impetus and strategic avenue for rural spatial commodification processes in the mountainous region of southwest China. As a crucial pathway for enhancing rural spatial value, the driving mechanisms and implementation approaches of rural spatial commodification require urgent theoretical elucidation. This study employs spatial production theory as its analytical framework and adopts a case study approach focusing on Zhongxin Village in the mountainous region of southwest China. Through in-depth interviews, participatory observations, and textual analyses, this study endeavors to unpack the intricate internal logic underpinning the process by which rural characteristic industries propel rural spatial commodification. The research findings demonstrate that under the collaborative mechanism of “government guidance–elite mobilization–villager participation–market penetration,” the systematic synthesis of regional resource endowments, cultural legacies, and market imperatives has culminated in the reconfiguration of local economic structures and the reproduction of rural landscapes. This study further elucidates the structural constraints and potential solutions encountered in the process of rural spatial commodification in southwest China’s mountainous hinterlands. This research provides region-specific implementation pathways for developing characteristic industries and advancing spatial commodification in these regions with geographical location disadvantages and weak economic development, offering significant policy implications for rural revitalization strategies.